2016
DOI: 10.1002/jcc.24476
|View full text |Cite
|
Sign up to set email alerts
|

A stress tensor and QTAIM perspective on the substituent effects of biphenyl subjected to torsion

Abstract: The Quantum Theory of Atoms in Molecules (QTAIM) defines quantities in 3D space that can be easily obtained from routine quantum chemical calculations. The present investigation shows that local properties can be related quantitatively to measures traditionally connected to experimental data, such as Hammett constants. We consider the specific case of substituted biphenyl to quantify the effects of a torsion φ, 0.0° ≤ φ ≤ 180.0°, of the C-C bond linking the two phenyl rings for C12 H9 -x, where x = N(CH3 )2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A recent review by Zhang et al gives an overview of the breadth of the field. For the purposes of electronic components, molecular junctions are of particular interest, which have been reviewed by Komoto et al Major breakthroughs have recently been reported, but a workable strategy remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Zhang et al gives an overview of the breadth of the field. For the purposes of electronic components, molecular junctions are of particular interest, which have been reviewed by Komoto et al Major breakthroughs have recently been reported, but a workable strategy remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…We propose to do this with the scalar and vector‐based aspects of the quantum theory of atoms in molecules (QTAIM) and the stress tensor formalism. In particular, we will use the QTAIM and stress tensor trajectory T σ ( s ) formalisms in the stress tensor trajectory space U σ to understand the functioning of the switch, previously used for benzene to present a new characterization of normal modes …”
Section: Introductionmentioning
confidence: 99%
“…The black plots; the relative energy ∆E for the undecorated biphenyl 19 and the BPLs were previously published by some of the current authors 4 but we include here as the BPL is the length of the r path that comprises the bond-path framework set = {p, q, r}. It can be seen that the form of the variation of the relative energy ∆E with the torsion θ is closer to that of the eigenvector-following path lengths than that of the corresponding variation of the BPL, compare The length exceed that of the BPL (path r) and can be seen from of the form of the path q i = r i + ε i e 2,i , where non-zero ellipticity ε values of the C4-C7 BCP result in values of the length > BPL.…”
mentioning
confidence: 99%
“…This is due to the presence of both the strong torsion bond that links the phenyl rings and the associated weak H---H bonding interactions. Recently, some of the current authors used the quantum theory of atoms in molecules (QTAIM) 2 and the stress tensor topological approaches to add to the long standing discussion about both the biphenyl 3 and substituted biphenyl molecule 4,5 . We explained the effects of the torsion θ of the C-C bond linking the two phenyl rings of the biphenyl molecule and demonstrated the favorable conditions for the formation of the H---H bonding interactions for a planar biphenyl geometry.…”
mentioning
confidence: 99%
“…Recently developed "next-generation" QTAIM (quantum theory of atoms in molecules) 9 has provided a set of tools to study the bond structure of molecular systems [4][5][6][7] , which can be used to improve our understanding of molecular switches. A recent investigation by some of the current authors 8 focussed on 3-imino-6methylenecyclohexa-1,4-diene-1,4-diamine that we referred to as the quinone switch, with F substituted in two locations (UP or DOWN) for the ring hydrogens and with and without a coordinated Fe atom above the ring, see Scheme 1.…”
mentioning
confidence: 99%